Therapeutic reassessment of first-line antiepileptic drugs in pediatric patients unresponsive to second-line agents: a randomized trial in Jakarta - Perdani, Roro Rukmi Windi; Mangunatmadja, Irawan; Arozal, Wawaimuli; Kaswandani, Nastiti; Handryastuti, Setyo; Medise, Bernie Endyarni; Wardani, Amanda Saphira; Thandavarayan, Rajarajan Amirthalingam; Oswari, Hanifah; Lee, Hee Jae (Paediatrica Indonesiana, 2025)
Background Epilepsy has a significant incidence in children, with 20-25% resistance to standard antiepileptic drugs (AEDs). Drug-resistant epilepsy (DRE) refers as the failure of two or more AEDs, either as monotherapies or in combination, to achieve seizure freedom, which includes the absence of all seizure types, even auras. Treatment algorithms for children with epilepsy range from starting with the lowest effective dose to using add-on or substitution therapy of AEDs. It usually started from using first-line AEDs (valproic acid, phenytoin, phenobarbital, carbamazepine) with titrated dose based on the patient condition, if seizure persist, another first-line AEDs may be added or substituted. Second-line AEDs (topiramate, levetiracetam, oxcarbazepine) are introduced when seizure persist despite optimal doses of first-line drugs with good compliance. Epilepsy treatment response is a dynamic process, not a fixed state. In some cases, repeating the medication cycle remains an option, as patient may initially appear drug-resistant but later respond to treatment. Thus, first-line AEDs may also serve as substitution therapy in children unresponsive to second-line agents as studies show comparable effectiveness between the two regimens. Objective To evaluate the efficacy and safety of first-line AEDs as substitution therapy (intentional replacement of patient’s current medication) in children resistant to second-line AEDs. Methods This 12-week, open-label, multicenter, randomized controlled trial was conducted in 91 epileptic children. Children aged 1 – 18 years with DRE, were randomized into the intervention (patients who received substitution therapy:  one AEDs was changed to first-line of AEDs) and control (patients who got standard therapy: one AEDs was changed to second-line of AEDs) groups. The primary outcome was the difference in the proportion of responders between the two groups. Secondary outcomes were analyzing the different improvements in quality of life (QoL), EEG feature, and time to achieve seizure reduction in both groups. The QoL was assessed by Quality of Life in Childhood Epilepsy Questionnaire 55 (QOLCE-55) to assess cognitive, emotional, social, and physical functions. Results There were no significant differences in the proportion of responders between the substitution therapy group (62.5%) and the standard therapy group (68.4%). Both groups experienced substantial reductions in seizure frequency, ranging from 78% to 80%. For further analysis, the average difference of seizure frequency before and after intervention was statistically significant in each group, it was P=0.000 in substitution group and P=0.00 in standard group. The analysis of quality of life showed the mean of total score in both groups was low even though the score was higher in the substitution group. For spesific function of quality of life, the cognitive and social function, was improved significantly in the group p<0.05). However, there were no significant differences of EEG improvement, seizure duration, time to achieve seizure frequency reduction, or adverse effects between the two groups. Conclusions First-line AEDs have comparable efficacy as second-line AEDs with mild to moderate adverse effects in DRE children. Thus, the repeated use of first-line AEDs as substitution therapy might be an option for children who resistant to second line AEDS.